Something lost along the way: changing patterns of leadership in Scottish residential schools - Mark Smith (Scottish Journal of Residential Child Care)
This article considers changing patterns of leadership in Scottish residential schools through the life histories of those who have undertaken leadership roles in the sector over the past 50 years. A case is made for the relevance of life history methods in offering a rich picture of the lived realities of residential child care over time. The stories are analysed to identify some features of leadership in the schools, locating these within the changing external policy environment. General trends from innovation towards regulation and from personalised towards standardised leadership practices are identified. The article employs wider theoretical insights to offer some evaluative comment on these changes, concluding that the path has not necessarily been one of untrammelled progress and that much of the value base and creativity that characterised earlier expressions of leadership has been lost along the way.